Applications of pre-emergent pyroxasulfone, flufenacet and their mixtures with triallate for the control of Bromus diandrus (ripgut brome) in no-till wheat (Triticum aestivum) crops of southern Australia. (February 2016) - Kleemann, Samuel G.L.; Boutsalis, Peter; Gill, Gurjeet S.; Preston, Christopher
Abstract: Four field experiments were conducted over a three-year period in Victoria and South Australia to investigate the effectiveness of pre-emergence (PRE) applications of pyroxasulfone, flufenacet and their mixtures with triallate for the control of Bromus diandrus in spring wheat. Herbicide mixtures of pyroxasulfone plus triallate and flufenacet plus triallate applied PRE to wheat provided consistently high levels of B. diandrus control (≥85%). In contrast, applications of pyroxasulfone and flufenacet applied alone along with trifluralin plus metribuzin (a common farmer practice in southern Australia) provided more variable control of B. diandrus (33–90%). Pyroxasulfone plus triallate treatments had a much lower (≤47 panicles m −2 ) panicle density of B. diandrus than trifluralin plus metribuzin (42–318 panicles m −2 ) and the non-treated control (118–655 panicles m −2 ). PRE herbicides which were safe to spring wheat and provided the greatest level of control of B. diandrus resulted in significantly ( P  < 0.05) higher grain yields at Culgoa (120%) and Gama (13%) than non-treated wheat (720 and 1740 kg ha −1 ). Although flufenacet was effective against B. diandrus, crop phytotoxicity at the higher dose (900 g ai ha −1 ) reduced spring wheat grain yield. Based on these results, PRE pyroxasulfone plus triallate could play an important role in the management of B. diandrus in spring wheat. However, high cost of these herbicides (AUS$35-$70 ha −1 ) may limit their adoption in low rainfall and low yielding wheat environments in southern Australia where B. diandrus is most prevalent. Highlights: Pyroxasulfone plus triallate and flufenacet plus triallate applied pre-emergence to wheat provided consistently high levels of Bromus diandrus control (≥85%). Pyroxasulfone and flufenacet alone along with common grower practice of trifluralin plus metribuzin provided more variable control (33–90%). Although flufenacet was effective against B. diandrus, crop phytotoxicity at the higher dose (900 g ai ha −1 ) reduced spring wheat grain yield. High cost of these herbicide mixtures (AUS$35-$70 ha −1 ) may limit their adoption in low rainfall and low yielding wheat environments in southern Australia.